2014
DOI: 10.1080/08856257.2014.891719
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Finnish teachers working with immigrant students

Abstract: Compared with many European countries, Finland has a shorter history of immigration. During the last 20 years, Finland has become a more multicultural society. Together with rising levels of immigration, teachers' concerns regarding how to manage an increasingly diverse school population have arisen. There are an increasing number of students with different cultural and native language backgrounds in Finnish schools. However, the school system is far from being an all-encompassing multicultural environment for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 35 publications
(39 reference statements)
0
34
0
2
Order By: Relevance
“…This lack of awareness amongst teachers of the impact of migration experiences and individual histories is compounded by the importance that teachers and educational policies place upon language acquisition. Research suggests that teachers frequently place primary emphasis on language acquisition rather than other elements of education or social support within schools (Riggs & Due, 2011; Sinkkonen & Kytalla, 2014). Such research indicates that mainstream teachers in general – compared with English language teachers in particular – hold the view that once the language of the relevant country has been acquired, other outcomes including satisfactory peer relationships will follow (Riggs & Due, 2011; Taylor, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This lack of awareness amongst teachers of the impact of migration experiences and individual histories is compounded by the importance that teachers and educational policies place upon language acquisition. Research suggests that teachers frequently place primary emphasis on language acquisition rather than other elements of education or social support within schools (Riggs & Due, 2011; Sinkkonen & Kytalla, 2014). Such research indicates that mainstream teachers in general – compared with English language teachers in particular – hold the view that once the language of the relevant country has been acquired, other outcomes including satisfactory peer relationships will follow (Riggs & Due, 2011; Taylor, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, the difference in perceptions of SMBs' difficulties between the teachers in this study and teachers in other international studies, was quite striking. In Swedish and Finnish studies, for example, language issues were considered the pivotal issue in SMBs' struggles, and the main cause of teachers' difficulties with trying to remedy SMBs' academic underachievement (Obondo, Lahdenperä, and Sandevärn 2016;Sinkkonen and Kyttälä 2014). However, this study found that the teachers' opinions about SMBs' Korean language capabilities tended to be ambivalent and contradictory.…”
Section: Sufficient Consideration Of the Multicultural Backgroundmentioning
confidence: 65%
“…This study discovered that many SMBs had issues in common, both at school and at home. The issues that arise in the education of SMBs were previously observed by a number of international research studies: academic underachievement (Bondy, Peguero, and Johnson 2017;Castles 2009;Martinez-Taboada et al 2017); language difficulty (Kang 2015;Obondo, Lahdenperä, and Sandevärn 2016;Sinkkonen and Kyttälä 2014;Suarez-Orozco and Suarez-Orozco 2009); importance of parental collaboration in IE (Angelides and Hajisoteriou 2013;Hamaidi, Homidi, and Reyes 2012;Lee and Low 2013;Soto-Chodiman et al 2012); and emotional difficulties and social isolation (Cherng 2015;Malsbary 2014;Plenty and Jonsson 2017). However, the difference in perceptions of SMBs' difficulties between the teachers in this study and teachers in other international studies, was quite striking.…”
Section: Sufficient Consideration Of the Multicultural Backgroundmentioning
confidence: 88%
“…The Scandinavian countries (Finland in particular) are often cited as models of education systems that value second language acquisition and at the same time perform well in international PISA testing, raising interest amongst linguists and educators about correlations between plurilingualism and academic success (see for example Sinkkonen & Kyttälä 2014;Jakonen-Kilpi 2012). However, the educational rationale here is clearly to work against a monolingualism that limits future prospects for young Scandinavians -the Finnish language being spoken only by the 5 million native speakers of Finland, learning other languages facilitates international opportunities.…”
Section: How Inclusive Are Language Education Policies In France and New Zealand?mentioning
confidence: 99%